The Effect of Music Therapy on the Sleep Quality of Patients with Heart Failure: The Miracle of Nature Music - Nahid Hosseini; Khatereh Seylani; Pegah Matourypour; Mehrdad Fakhrodini; Hamid Haghani; Masoumeh Zakerimoghadam (Iranian Journal of Nursing and Midwifery Research, 2024)
Background: Patients with heart failure experience poor sleep quality due to the nature of disease they suffer from. The aim of this study was to investigate the effect of music on the sleep quality of patients with heart failure. Materials and Methods: The present study is a randomized clinical trial, which was performed on 76 patients with heart failure, hospitalized in the cardiac ward of an educational hospital. These patients had obtained a score of 5 or higher on Pittsburgh’s sleep quality index. The block randomization method was used to generate the allocation sequence. Thus, the number of subjects in each block was determined to be 4 people in 18 blocks. Intervention was collection of nature music played through headphones for 30 minutes over three nights, and at the end of the third night, the Pittsburgh’s index was completed again by both groups. Data were analyzed using descriptive and inferential statistics. Results: After the intervention, the mean scores of mental quality of sleep (p = 0.007) and daily function disorders improved significantly in the intervention group (p = 0.025). Significant differences were seen between the mean scores of mental quality of sleep (p < 0.001), daily function disorders (p = 0.002), delay in falling asleep (p = 0.01), sleep disorders (p < 0.001), and use of sleeping pills (p < 0.001) before and after the intervention in the intervention group. Conclusions: Playing relaxing music like nature sounds and spending time in nature after discharge can improve the sleep quality and sense of relaxation in patients with heart failure. The implementation of such affordable and amusing interventions can be proposed by nurses in heart failure patients.